The Influence Of Total Quality Management (TQM), Performance Measurement System, Reward System And Organizational Culture On Managerial Performance (Case Study At PT. Pos Indonesia (Persero) Jambi City) - Mutiya, Aprillia; Yuliusman, Yuliusman; Yustien, Reni (Jurnal Cakrawala Akuntansi, 2024)
This study aims to provide empirical evidence on the influence of Total Quality Management (TQM), performance measurement systems, reward systems, and organizational culture—both simultaneously and partially—on managerial performance. The research was conducted at PT Pos Indonesia (Persero) in Jambi City, with a sample of 46 respondents selected using purposive sampling. Data were analyzed using multiple linear regression, supported by validity and reliability tests, classical assumption tests, and hypothesis testing. Data processing was carried out using SPSS version 22 for Windows.The findings reveal that TQM, performance measurement systems, reward systems, and organizational culture, when tested simultaneously, have a significant influence on managerial performance. However, when examined partially, only TQM and reward systems demonstrate a statistically significant effect on managerial performance, whereas performance measurement systems and organizational culture do not show a significant impact.This study contributes to organizational performance literature by confirming that quality management practices and effective reward mechanisms are essential drivers of managerial performance. In contrast, the lack of significant influence from performance measurement systems and organizational culture suggests the need for deeper structural alignment and cultural reinforcement within the organization. Practically, the results offer strategic insights for companies aiming to enhance managerial effectiveness through quality-centric management and motivational incentives.